Ways and Methods of Managing Reduction of Unfinished Construction Projects in Industry - E. V. Gavrilin; A. E . Gavrilin (Управленческие науки, 2022)
The paper depicts ways and means of solving one of the key problems that the Government of the Russian Federation has identified as a priority in 2020 and for subsequent years. This includes the reduction of unfinished construction projects (UCP), the financing of the construction of which was carried out at the expense of the federal budget, in particular, industrial facilities without attracting additional budget allocations. The purpose of the work is to create a management mechanism that allows in a short time to involve in the economic turnover of UCP, the construction of which was carried out at the expense of the federal budget. Within the framework of existing regulatory and legislative rules and restrictions, the mechanism comprises methods that allow organizing the transfer of property to another level of ownership, privatization, completion of construction at the expense of extra-budgetary sources, as well as write-off and disposal for UCP. The proposed ways and methods of management make it possible to involve the maximum number of UCP in the economic turnover in the shortest possible time. Federally owned objects that have not aroused interest in the regions and that lack investment attractiveness for private investors should be completed at the expense of the federal budget, or written-off and disposed of. The authors used the described methods in fulfilling the instructions of the Government of the Russian Federation to reduce the UCP and allowed to increase several times the number of involved projects compared to previous periods.